KUDA-KUDA PENCAK SILAT DALAM PENCIPTAAN TARI JI KARYA GALUH PUSPITA SARI PADA TAHUN 2018 DI GEDUNG TEATER BESAR ISI SURAKARTA - Galuh Puspita Sari; Matheus Wasi Bantolo (Greget, 2019)
JI Dance Works is a new choreography work that departs with the basic motion of horses on the Pencak Silat as well as the phenomenon of binary opposition in life in which two things both have the meaning of balance in his achievements. The problem that will be discussed in this research is how the concept of binary opposition and Pencak Silat in the creation and how to form the dance works. To outline the creation problem using the concept of Alma M. Hawkins strengthened by the creation of contemporary dance according to Matheus Wasi Bantolo and the cultivation of Pencak Silat moves to dance according to Mathias Supriyanto. This writing and assessment use practice based research method with qualitative basis of interpertative destriptif, with participant action research process. The process of creation in JI dance Works is based on Observation, improvisation, composition and evaluation techniques. JI Dance works in a pair of choreography with a fighting theme As the concept of binary opposition in the life and the design of the basic motion of horses in the Pencak Silat as a source of the idea of creation and combined with the concept of binary opposition as inspiration by taking the essence of balance of both things t Telecast. The motion developed through the basic motion of horses, styles, and also the Kembangan (art of fighting) is found in the PSHT Pencak Silat College. Developing the basic motion of Pencak Silat into the dance by searching for similarities, from the shape of horses to Pencak Silat with the shape of the climb on the dance that was given the science of choreography such as levelgiving, volume, and the creation of the atmosphere in the dish Combined with the possibility of dance music and the Nglambari. Keywords: kuda-kuda Pencak Silat, JI dance, binary opposition.